Tumor cell dissemination: emerging biological insights from animal models and cancer patients - Kang, Yibin; Pantel, Klaus (Cancer cell, 2013)
Circulating tumor cells (CTCs) and disseminated tumor cells (DTCs) are increasingly recognized for their potential utility in disease monitoring and therapeutic targeting. The clinical application of CTC/DTC requires better understanding of the biological mechanisms behind tumor dissemination, the survival of DTCs, and their activation to aggressive growth from dormancy. Recent research using animal models of DTCs and CTCs have provided novel insights into these processes. Here, we discuss these findings in the context of results obtained from the clinical analyses of CTCs and DTCs, which demonstrate that the animal models mimic, in many aspects, the complex situation in patients.